2021
DOI: 10.21037/tau-21-232
|View full text |Cite
|
Sign up to set email alerts
|

High TNFSF13B expression as a predictor of poor prognosis in adrenocortical carcinoma

Abstract: Background: Adrenocortical carcinoma (ACC) is an extremely rare malignant tumor with poor prognosis.Existing treatment options have limited effects, and new therapeutic targets urgently need to be discovered. TNFSF13B has been reported to be associated with the prognosis of clear cell renal cell carcinoma, but it has not been studied in ACC.Methods: TNFSF13B expression was analyzed and compared between ACC tumors and normal tissues by using public datasets from TCGA and GTEx. Kaplan-Meier analysis was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…[ 9 ] However, TNFSF13B has also been reported to exert a pivotal role in several other diseases, including neoplasia, such as breast cancer, glioblastoma, melanoma, and adrenocortical carcinoma. [ 10 , 11 , 12 , 13 ] Moreover, TNFSF13B is reported to enriched in tumor with hyperplastic blood vessels, and regarded as a biomarker for the metastases. [ 14 , 15 ] These data reinforced that TNFSF13B may play a key role in the progression of renal cell carcinoma, as RCC is strongly vascularized.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] However, TNFSF13B has also been reported to exert a pivotal role in several other diseases, including neoplasia, such as breast cancer, glioblastoma, melanoma, and adrenocortical carcinoma. [ 10 , 11 , 12 , 13 ] Moreover, TNFSF13B is reported to enriched in tumor with hyperplastic blood vessels, and regarded as a biomarker for the metastases. [ 14 , 15 ] These data reinforced that TNFSF13B may play a key role in the progression of renal cell carcinoma, as RCC is strongly vascularized.…”
Section: Introductionmentioning
confidence: 99%
“…As a B lymphocyte stimulator, it is important for the survival, proliferation, and differentiation of B cells ( 24 ). In addition, TNFSF13B effectively promotes the apoptosis of various tumor cells, such as human lymphoma cells (U937), prostate cancer cells (PC-3), colon cancer cells (HT-29), cervical cancer cells (HeLa), breast cancer cells (MCF-7), and embryonic kidney cells (A293) ( 25 ). Previous studies have confirmed that TNFSF13B can not only predict the prognosis of ccRCC patients, but is also an important mediator of information transmission between tumor cells and the tumor microenvironment, and is a potential therapeutic target ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…A GSEA is used to evaluate the distribution trend of genes in a pre-defined gene set in a gene table ranked by the phenotype correlation to determine their contribution to the phenotype ( 23 ). We obtained the background gene sets of “c2.kegg.v7.4.symbols” and “c5.go.v7.4.symbols” from the MSigDB ( 24 ) database, and we used the “clusterprofiler” R package to perform the GSEA ( 25 ). In this analysis, P<0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…As an important B lymphocyte stimulator, it is important for the survival, proliferation and differentiation of B cells (22). In addition, TNFSF13B can effectively promote the apoptosis of various tumor cells, such as human lymphoma cells (U937), prostate cancer cells (PC-3), colon cancer cells (HT-29), cervical cancer cells (HeLa), breast cancer cells cells (MCF-7) and embryonic kidney cells (A293) (23).…”
Section: Discussionmentioning
confidence: 99%